WORD PLAY AS A MEANS OF MANIPULATION IN THE ENGLISH PRESS - Ustinova, Olga (Revista Inclusiones, 2020)
Word play is one of the most controversial phenomena in the modern linguistics. This is due to the fact that it is based on linguocultural realities and stereotypes, which makes it difficult to understand for the representatives of the foreign language culture. However, despite this, there is no doubt that the main function of any pun is attractive. That is why the word play is often used in the various mass media. In this article, the author analyzes the word play from the point of view of one of the means of manipulating public consciousness in the English-language press. In addition, both basic and secondary functions of the English word play are analyzed. The author analyzes the tactics used to manipulate public consciousness.